2017
DOI: 10.1111/ecc.12704
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating early diagnosis of lung cancer amongst primary care patients: The views of GPs

Abstract: Early diagnosis of lung cancer (LC) is a policy priority. However, symptoms are vague, associated with other morbidities, and frequently unrecognised by both patients and general practitioners (GPs). This qualitative study, part of a larger mixed methods study, explored GP views regarding the potential for early diagnosis of LC within primary care. Five focus group discussions (FGDs) were conducted with GPs (n = 16) at primary care practices (n = 5) across four counties in south England. FGDs were audio‐record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 21 publications
1
35
0
Order By: Relevance
“…Some studies 47,78,[80][81][82] only examined the overall effect of any disease (rather than specific diseases) on the diagnostic process ( Figure 1).…”
Section: Diagnostic Process Referrals and Use Of Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies 47,78,[80][81][82] only examined the overall effect of any disease (rather than specific diseases) on the diagnostic process ( Figure 1).…”
Section: Diagnostic Process Referrals and Use Of Investigationsmentioning
confidence: 99%
“…On the other hand evidence on the effects of specific chronic diseases is provided by several studies 2,46,66,69,70,72,73,79,[82][83][84][85] . In particular, congestive heart failure or coronary artery disease can lead to missed opportunities to refer patients promptly for endoscopic examination 84 , despite symptoms of colorectal cancer.…”
Section: Diagnostic Process Referrals and Use Of Investigationsmentioning
confidence: 99%
“…Factors associated with later presentation include limited awareness of cancer symptoms and fear of cancer,6 concerns about wasting their own and general practitioners’ time,7 and stoicism and stigma around smoking 8…”
Section: How Can We Improve Symptom Awareness In People At Risk?mentioning
confidence: 99%
“…Furthermore, one study has found that GPs readiness to act on symptoms is associated with improved cancer survival, and that Swedish GPs are more prone to act on symptoms than for example GPs in UK [37]. Nevertheless, GPs sometimes fail to recognize specific alarm symptoms [38], indicating that GPs do not respond directly to symptoms as objective things and that GPs assign meanings to symptoms by interacting with patients. Besides, since the introduction of CPPs the playing field has changed, meaning that GPs now have to match their knowledge through interacting with CPPs', not only with patients.…”
Section: Discussionmentioning
confidence: 99%